The therapeutic potential of ultra-short-acting β-receptor antagonists in perioperative analgesic: Evidence from preclinical and clinical studies - Fu, Linbin; Yu, Buwei; Li, Zheng; Liu, Zhiheng (Frontiers in Pharmacology, 2022)
Perioperative multimodal analgesia can reduce the side effects of a high concentration of opioids, improving the comfort of the patient. However, the insufficient analgesia of this model has prompted researchers to explore new adjuvant analgesics. Recently, an increasing number of studies has found a low-grade analgesic effect in the clinical application of short-acting β-adrenergic receptor antagonists, which are conventionally used as pharmacologic agents in the cardiovascular system. The mechanism by which short-acting β-antagonists exert antinociceptive effects has not yet been clarified. In this review, we intended to address its potential reasons from the side of neurotransmitters, inflammatory cytokines, and signaling pathways, providing theoretical proof to the application of β-adrenergic receptor antagonists in analgesia.